Typhoid ileal perforation: a two-year study at a tertiary care hospital of South India - Markapuram, Kishore Kumar; Rachamalla, Ramalinga Reddy; Satish, Sreeram; Kandati, Jithendra (International Surgery Journal, 2018)
Background: Typhoid fever is an acute febrile illness caused by gram negative bacilli, Salmonella enteritidis serovars typhi. The incidence of typhoid fever varies globally from 140 episodes per 10000-person years in Kolkata to 273 per 10000 in Delhi, India. The present study was done with an aim to assess the risk factors, complications and different surgical techniques in cases of typhoid ileal perforation. The study also identifies and focuses on the post-operative complications in cases of perforation due to typhoid fever. Methods: A prospective study was conducted for a period of two years from June 2105 to May 2017 at a tertiary care hospital on all the cases admitted and operated for typhoid perforation. The data collected was analyzed using SPSS version 15.0 for windows 7. Results: 104 cases with an incidence rate of 8.4% of perforation were included in the study. Males were majority and mean age of the study group was 21.8±10.1 years. The peak incidence of study group was 31-40 years and >60 years. Fever and abdominal pain (rebound tenderness) was the common sign and symptoms. Free fluid and air collection under the diaphragm was the commonest finding in radiographs and ultrasound. Majority of the cases had single perforation (84.62%) and ileum was the most common site of perforation (84.62%). Simple closure with double layering was the commonest surgical procedure performed and the incidence of post-operative complication was 36.5%. Overall mortality in the study was 3.8%. SSI was the commonest post-operative complication. Conclusions: To conclude from our study, typhoid still remains as an endemic disease in spite of improved awareness and better sanitation facilities. Inadequate treatment, misdiagnosis and mismanagement of cases by non-medical practitioners at rural settings may increase the risk of complications